2019
DOI: 10.24925/turjaf.v7i4.588-592.2247
|View full text |Cite
|
Sign up to set email alerts
|

Survival Survey of Lactobacillus acidophilus In Additional Probiotic Bread

Abstract: Bread is a popular food in the world because of its variety and convenience. Currently, studies on the adding probiotics to bread are limited due to the adverse effects of processing, such as baking temperature, aerobic environment to the probiotic bacteria. The objective of this study was to produce probiotic cream bread, in which Lactobacillus acidophilus was microencapsulated with Alginate 2% (A); Alginate 2% + maltodextrin 1% (AM); Alginate 2% + xanthan gum 0.1% (AX); and Alginate 2% + maltodextrin 1% + xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In a similar study, Zhang et al [ 4 ] observed that the survival of L. plantarum significantly decreased to 104~5 CFU/g after bread baking at 180 °C for 5 min. Our results agree with Thang et al [ 25 ], showing the viability of L. acidophilus encapsulated in a combination of alginate and xanthan gum was decreased by 3.64 log CFU/g during baking compared to non-capsulated, which was about reduced 5 logs CFU/g.…”
Section: Resultssupporting
confidence: 93%
“…In a similar study, Zhang et al [ 4 ] observed that the survival of L. plantarum significantly decreased to 104~5 CFU/g after bread baking at 180 °C for 5 min. Our results agree with Thang et al [ 25 ], showing the viability of L. acidophilus encapsulated in a combination of alginate and xanthan gum was decreased by 3.64 log CFU/g during baking compared to non-capsulated, which was about reduced 5 logs CFU/g.…”
Section: Resultssupporting
confidence: 93%
“…Thang et al. (2019) also observed a significant reduction in Lactobacillus acidophilus probiotic cells after baking bread. Other researchers also showed increased thermal stability of probiotic bacteria by encapsulation process (Calderón‐Oliver et al., 2020).…”
Section: Resultsmentioning
confidence: 93%
“…These researchers said that the material type used for the encapsulation wall had a significant effect on the survival of probiotics. Altamirano-Fortoul et al (2012) also found that the susceptibility of probiotic bacteria depends on the microcapsules nature Thang et al (2019). also observed a significant reduction in Lactobacillus acidophilus probiotic cells after baking bread.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…As a result, the number of published studies about the probiotication of baked goods has been low in the past five years [ 15 , 16 , 17 , 18 , 19 , 20 ]. Generally, the incorporation of microencapsulated probiotic cells in bakery production was covered by three approaches: (1) in cream or filling materials, (2) addition to cake mix or dough, and (3) the distribution of powdered cells on the surface of the dough before baking.…”
Section: Food Probiotication With Microencapsulated Cellsmentioning
confidence: 99%